The Analysis of Organic Matter In Sediment and Macrozoobenthos Abundance in the Coastal Water of Selat Panjang Strait Meranti Islands Province Riau - Barnes Silitonga; Syahril Nedi; Yusni Ikhwan Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACT This research was conducted in July 2014 in the waters of Selat Panjang Strait Meranti Islands Riau Province The goal was to analyze the content of organic matter in the sediments and benthic organism. The study was also to observete relationship betwen organic material content of sediments and macrozoobenthic abundance. The sample were collected from 5 points station consist of three sub station. Sampling direct research at low tide with 3 repetitions. The parameters measured in this study were the brightness, water temperature, salinity, current velocity, and pH. The results of this study indicated that the environmental conditions of Selat Panjang Strait still able to support macrozoobenthic life. The macrozoobenthos found were as many as 15 species consisting of 2 Phyla, namely the Molluscs and Oligochaetes. There were two classes in the phylum of Mollusc 6 species of bivalves and gastropods 8 and 1 species of phylum class Oligochaete Tubificinae. The diversity index (H') was low, where the number of individuals was not uniform. The dominance index (C) close to 1 meaning that the community was dominated by a certain type or species. The relationship with the organic matter content in the waters showed weak and positive meaning if the organic material increases the abundance also increased.. Kata Kunci: Macrozoobenthos, Meranti island, Abundance, and Organic matter